Radioactivation Control of Energy and Number of Protons and Deuterons Collectively Accelerated in Luce Diodes - Ryzhkov V. A. Vladislav Andreevich; Zhuravlev M. V. Mikhail Valerievich; Pyatkov I. Igor; Lopatin V. S. (New Accelerator Systems and Tools for Materials Research. Oral Presentation, 2019)
Заглавие с экрана